Chronic high‐dose testosterone treatment: impact on rat cardiac contractile biology. Issue 14 (28th July 2019) - Wadthaisong, Munthana; Witayavanitkul, Namthip; Bupha‐Intr, Tepmanas; Wattanapermpool, Jonggonnee; de Tombe, Pieter P.
Abstract: Androgen therapy provides cardiovascular benefits for hypogonadism. However, myocardial hypertrophy, fibrosis, and infarction have been reported in testosterone or androgenic anabolic steroid abuse. Therefore, better understanding of the factors leading to adverse results of androgen abuse is needed. The aim of the present study was to examine the impact of high dose of androgen treatment on cardiac biology, and whether exposure duration modulates this response. Male rats were treated with 10 mg/kg testosterone, three times a week, for either 4 or 12 weeks; vehicle injections served as controls. Four weeks of testosterone treatment induced an increase in ventricular wall thickness, indicative of concentric hypertrophy, as well as increased ejection fraction; in contrast, both parameters were blunted following 12 weeks of high‐dose testosterone treatment. Cardiac myocyte contractile parameters were assessed in isolated electrically stimulated myocytes (sarcomere and intracellular calcium dynamics), and in chemically permeabilized isolated myocardium (myofilament force development and tension‐cost). High‐dose testosterone treatment for 4 weeks was associated with increased myocyte contractile parameters, while 12 weeks treatment induced significant depression of these parameters, mirroring the cardiac pump function results. In conclusion, chronic administration of high‐dose testosterone initially induces increased cardiac function. However, this initial beneficial impact is followed by significant depression of cardiac pump function, myocyte contractility, and cardiac myofilament function. Our results indicate that chronic high‐testosterone usage is of limited use and may, instead, induce significant cardiac dysfunction. Abstract : Testosterone exerts many beneficial cardiovascular functional effects. However, abusive testosterone treatment might cause serious cardiac complications. This study demonstrates that physiological cardiac hypertrophy adaptation seen after a first period of supraphysiological testosterone treatment, reversed to a detrimental impact following long‐term treatment. The cellular mechanisms underlying this phenomenon involved both intracellular Ca 2+ homeostasis and myofilament function. Our results indicate that chronic high‐testosterone usage is of limited use and may, instead, induce significant cardiac dysfunction.